The incorporation of an object oriented development approach for the construction of a community based health information system - Pervan, Graham; Mcdermid, Donald (Health Informatics Society of Australia, 1998)
Substantial national and international resources have been invested in the research and development of a number of health information models, eg. the National Health Information Model (NHIM), the NSW Health Community Health Information Model (CHIM), the American Joint Working Group for a Common Data Model (JWG-CDM) and the CEN (Comite Europeen de Normalisation) European Healthcare Record Architecture. These models have greatly assisted in the development of standard data definitions and structure, they primarily address the data requirements of an organisation and have been developed through the identification of agreed patterns of data.In Australia the NHIM has introduced a framework for health information modelling to improve theoverall information standards and support in the health industry, and the CHIM has obtained substantialendorsement as a representation of community health data. Both of these models have been developed usingEntity-Relationship (ER) techniques. An iterative approach across organisational boundaries has been takenin the development of these models focusing on the identification of common patterns of data. Thedevelopment of information systems to support the health organisations, based on these models, requires substantial further consultation to identify the business patterns, functional and physical design requirements.The Community Health Information Enterprise (CHIME), incorporating the CHIM, has undertaken thefurther consultation required and is currently utilising an Object-Oriented Programming (OOP) approach.This paper provides an insight into community based health, discusses the development approach and further proposes an information framework that extends the Object-Oriented approach to the design phase.